Rapid Detection of Mycobacterium tuberculosis in Contaminated BACTEC 12B Broth Cultures by Testing with Amplified Mycobacterium Tuberculosis Direct Test - Zheng, Xiaotian (American Society for Microbiology, 2001)
Contamination of broth cultures of acid-fast bacilli (AFB) by bacterial species other than Mycobacterium species frequently occurs. Many of these contaminated cultures require redecontamination and reincubation before the appropriate tests can be performed for identification, significantly affecting the turnaround time for reporting culture results. In this study, the Amplified Mycobacterium Tuberculosis Direct Test (MTD; Gen-Probe) was performed to detect the Mycobacterium tuberculosis complex (MTBC) in 125 BACTEC 12B broth cultures with positive growth indices. Among these, 41 grew non-AFB bacteria only, and all 41 were negative by the MTD. The remaining 84 bottles contained contaminated cultures that grew both AFB and other bacteria or yeasts. Repeat decontamination and reincubation of these specimens required a mean time of 13 days (range, 3 to 40 days). The MTD results were positive for 10 samples, 9 of which were MTBC culture positive and 1 of which grew Myobacterium celatum, a species known to cross-react in the MTD. All cultures growing other mycobacterial species were negative by the MTD. The results of this study demonstrate that the MTD is both sensitive and specific in detecting MTBC in contaminated broth cultures and that, when used selectively, the MTD can potentially rule in or out a diagnosis of MTBC as much as 12 days earlier than using nonamplified DNA probe testing alone can.